Resveratrol ameliorates physical and psychological stress-induced depressive-like behavior - Chrismawan Ardianto, - (Walter de Gruyter GmbH, 2021)
Objectives Depression is a mental disorder that profoundly affects all aspects of life, but currently, antidepressants have some problems with their effectiveness and side effects. Resveratrol is a compound that has the ability to regulate the hypothalamic-pituitary-adrenal axis. This study aimed to determine resveratrol’s effect on physical and psychological stress-induced depressive-like behavior.